2018
DOI: 10.1021/acs.iecr.8b02739
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linked Poly(ethylene oxide) Ion Gels Containing Functionalized Imidazolium Ionic Liquids as Carbon Dioxide Separation Membranes

Abstract: d i m i d a z o l i u m b i s -(trifluoromethylsulfonyl)imide (Tf 2 N) ionic liquids (ILs) were incorporated at 40 and 60 vol % loading into a crosslinked poly(ethylene oxide) polymer network to create ion gels for carbon dioxide (CO 2 )-selective gas separation membranes. The ILs plasticize the poly(ethylene oxide)-based polymer to increase its gas permeability. Compared to the base polymer, with a CO 2 permeability of 145 barrer and a CO 2 against nitrogen (N 2 ) selectivity of 47, the highest CO 2 permeabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…[55]. The literature values are illustrated for comparison purposes and were taken from: (□) [12], (∆) [37] and (o) [20,22,[34][35][36].…”
Section: Co 2 /N 2 Separation Performancementioning
confidence: 99%
See 2 more Smart Citations
“…[55]. The literature values are illustrated for comparison purposes and were taken from: (□) [12], (∆) [37] and (o) [20,22,[34][35][36].…”
Section: Co 2 /N 2 Separation Performancementioning
confidence: 99%
“…The ILs consisting of an aromatic cation with acid proton (imidazolium and pyridinium) and a low basicity anion ([TFSI] − ) imparted the most stable and miscible iongel membranes and led to significant increases in gas permeability [34]. Later on, Kusuma et al [35] extended their study by incorporating a series of 1,3-substituted imidazolium [TFSI] ILs (at 40 and 60 vol.% loading) into a polymer network consisting of two monomers, the ethoxylated (20) trimethylolpropane triacrylate and the 3,6-dioxa-1,8-octanethiol. The results demonstrated that terminal substituents such as hydroxyl, benzyl, nitrile or trimethylsilyl can decrease chain mobility and/or reduce the free volume cavity site, while short alkyl or alkoxy chains can significantly increase gas permeability through the iongels studied, with [C 2 mim] + being the most effective cation [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogous to the Pebax ® physically crosslinked poly(ether-amide) block copolymers, chemically cross-linked polyether-based ion gels were reported as well. Among twelve different ILs, the terminal substituent of the cation was found to determine most the extent of improvement of the gas permeability, and shorter substituents proved most effective because they were able to guarantee the highest charge density [ 297 ] in ethoxylated trimethylolpropane triacrylate-based ion gels. On the other hand, when varying the polymer network structure, a lower cross-link density tends to yield a higher permeability because it allows the incorporation of more [EMIM][Tf 2 N].…”
Section: Polymer/il Blends; Ion Gelsmentioning
confidence: 99%
“…Over the past two decades, ionic liquids (ILs) and poly(ionic liquid)s (PIL)s have raised great interest as highly tuneable materials to improve existing membrane-based CO2 separation processes, delivering a wide range of membranes with different chemical structures, physical/chemical properties, morphologies and separation performances. [13][14][15] Different strategies have been used towards the development of IL-based membranes, such as supported ionic liquid membranes (SILMs), 16,17 polymer/IL composite membranes, 18,19 ion gel membranes, [20][21][22] or the fabrication of PIL/IL composite membranes. [23][24][25] In particular, the incorporation of ILs into PILs is an attractive strategy to obtain membranes with liquid-like gas transport properties, while maintaining a good mechanical stability.…”
Section: Introductionmentioning
confidence: 99%